Evaluation of two molecular detection platforms for gastroenteritis pathogens in treated sewage water in the Eastern province of Saudi Arabia - Fawaz A. Al-Wohaib; Ibtihaj Al-Sharif; Hassan Al-Zain; Donna Murad; Layla Al-Harbi; Maha Al-Mozaini (Scientific Reports, 2022)
Abstract The ability to screen environmental water samples for gastroenteritis pathogens, particularly viruses remains challenging. Here, we investigated the presence of enteric viruses in treated sewage effluent water samples collected from a cooling tower in The Kingdom of Saudi Arabia (SA) from 2018 to 2019. Our ultimate aim was to determine the optimal handling and processing conditions for the water samples and the most sensitive detection method for the assessment of viral contamination. Sewage was collected before and after treatment at three defined zones. Samples were concentrated by ultracentrifugation and analyzed using a multiplexed bead-based assay system (Luminex technology) or multiplex PCR (QIAstat-Dx). The efficiency of these modalities to accurately detect virus contamination were subsequently compared. In total, 64 samples (16 controls and four treated samples per-control) were analyzed for 26 enteric pathogens. Of the samples, 98.7% were negative for viruses following treatment. Detection rates were higher for the multiplex PCR (QIAstat-Dx) system compared to the hybridization method, highlighting its higher sensitivity. The current water sewage treatment protocols in KSA could efficiently eradicate viral pathogens, minimizing their potential for waterborne transmission. We provide the first systematic analysis of two molecular detection methods for the assessment of gastroenteritis-associated pathogens from environmental samples in KSA. We conclude that the multiplex PCR (QIAstat-Dx) system outperforms the Luminex technology for the detection of virus pathogens in treated water samples.